Putting Life in Years (PLINY) : a randomised controlled trial and mixed-methods process evaluation of a telephone friendship intervention to improve mental well-being in independently living older people /: a randomised controlled trial and mixed-methods process evaluation of a telephone friendship intervention to improve mental well-being in independently living older people. (December 2014) - Hind, D (Daniel)
No abstract available